2018
DOI: 10.1007/s11187-018-0052-2
|View full text |Cite
|
Sign up to set email alerts
|

The cost of injustice: overall justice, emotional exhaustion, and performance among entrepreneurs: do founders fare better?

Abstract: This is the accepted version of a paper published in Small Business Economics. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 88 publications
(97 reference statements)
2
18
0
Order By: Relevance
“…Regarding the ownership stake, we could not find studies dealing with its link with burnout except Lechat and Torrès (2016), who argued that an increase in financial involvement generates additional stressors, 6 and Soenen et al (2019), who found a link between entrepreneurial burnout and firm performance.…”
Section: Controlsmentioning
confidence: 73%
See 2 more Smart Citations
“…Regarding the ownership stake, we could not find studies dealing with its link with burnout except Lechat and Torrès (2016), who argued that an increase in financial involvement generates additional stressors, 6 and Soenen et al (2019), who found a link between entrepreneurial burnout and firm performance.…”
Section: Controlsmentioning
confidence: 73%
“…We also consider the size of the business (in terms of employees) and the growth of turnover, and their possible relationship with burnout (Hatak et al, 2015;Soenen et al, 2019). The seminal work of Mintzberg (1979) made a connection between business size and stressors.…”
Section: Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elst et al (2014) proposed that employee emotional exhaustion in the workplace is an indicator of well-being at work, which is manifested by the exhaustion of an individual's feelings for a certain thing (Chang, 2009). As a result, employees have negative experiences and negative work emotions, such as impaired self-esteem, depression, nervousness, and irritability (Guillaume et al, 2018). In addition, employees with state anxiety tend to exhaust their energy and attention to worry about taskrelated issues and criticize their abilities (Sarason, 1984).…”
Section: Employees' Organizational Citizenship Anxiety and Well-beingmentioning
confidence: 99%
“…However, a study by Souder et al (2012) suggested that compared with professional CEOs, founder CEOs are less likely to engage in market expansion. Further, researchers find that the dispositional characteristics of a founder CEO—such as achievement orientation and locus of control (Sebora, Lee, & Sukasame, 2009), positive affect (Baron, Tang, & Hmieleski, 2011), and justice perceptions (Soenen, Eib, & Torrès, 2019)—positively affect entrepreneurial venture performance. In addition, founder CEO's social ties (friendship ties) are positively related to new firm performance (Roberts & Sterling, 2012), but the founder's wealth is negatively related to startup performance (Hvide & Møen, 2010).…”
Section: Founder‐ceo Research Themesmentioning
confidence: 99%